The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11999-017-5339-0
|View full text |Cite
|
Sign up to set email alerts
|

Readability of Orthopaedic Patient-reported Outcome Measures: Is There a Fundamental Failure to Communicate?

Abstract: Fears of widely incomprehensible PROMs may be unfounded. Future research to identify the most appropriate readability algorithm for use in the healthcare sector, and revalidation of PROMs after readability-improving edits is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 99 publications
(41 reference statements)
0
41
0
Order By: Relevance
“…orthopedics, oncological surgery) and represent a cutting edge opportunity for pain physicians to influence rational evidence-based pain care. [23][24][25][26][27] A scoping review characterized 21 publications where PROMIS measures were used in the perioperative setting. The authors applauded the utility of PROMIS measures to provide standardized, accurate and efficiently captured patient constructs.…”
Section: Quality Of Recovery Score (Qor) -Qor-9 Qor-15 Qor-40mentioning
confidence: 99%
“…orthopedics, oncological surgery) and represent a cutting edge opportunity for pain physicians to influence rational evidence-based pain care. [23][24][25][26][27] A scoping review characterized 21 publications where PROMIS measures were used in the perioperative setting. The authors applauded the utility of PROMIS measures to provide standardized, accurate and efficiently captured patient constructs.…”
Section: Quality Of Recovery Score (Qor) -Qor-9 Qor-15 Qor-40mentioning
confidence: 99%
“…The readability of patient-oriented materials has been a common subject in recent orthopedic literature,5, 7, 11, 19, 25 and most studies have found that very few online documents are written at an appropriate level 2, 6, 31, 32, 35. Although print material may be accessed less frequently than online material, a Pew survey found that nearly 60% of people who initially learn about their diagnoses online eventually see a clinician 8 .…”
mentioning
confidence: 99%
“…15,16 Recent studies in other healthcare fields, including medical oncology and orthopedics, have measured readability scores with widely ranging results. 17,18 Within otolaryngology, prior readability studies of PROMs have analyzed those used for audiology and dysphagia only. 1,19,20 No prior studies have evaluated H&N PROMs.…”
Section: Introductionmentioning
confidence: 99%